TRAIL-Mediated Suppression of T Cell Receptor Signaling Inhibits T Cell Activation and Inflammation in Experimental Autoimmune Encephalomyelitis - Chyuan, I-Tsu; Tsai, Hwei-Fang; Wu, Chien-Sheng; Sung, Chi-Chang; Hsu, Ping-Ning (Frontiers in Immunology, 2018)
Objective: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) induces cell apoptosis by transducing apoptosis signals after interacting with its receptor (TRAIL-R). Although the actual biological role of TRAIL remains to be elucidated, recent accumulating evidence implies that TRAIL regulates immune responses and immune cell homeostasis via an apoptosis-independent pathway, suggesting a novel immune-regulatory role of TRAIL in autoimmune diseases. The purpose of this study is to address the immune-regulatory role and molecular mechanism of TRAIL in regulating T cell activation in autoimmune diseases. Design: TRAIL was administered to mice to induce experimental autoimmune encephalomyelitis (EAE), and to evaluate its impact on neuroinflammation and disease activity. The effects of TRAIL on neuro-antigen (MOG35-55)-activated T cell proliferation and cytokine production were investigated. TRAIL- treated MOG35-55-activated splenic Th17 cells were further adoptively transferred into Rag1 KO mice to induce passive EAE. Gene expression profiles of CD4+ T cells from EAE mice treated with TRAIL were analyzed by RNA sequencing and transcriptome analysis. Results: TRAIL suppressed autoimmune encephalomyelitis and inhibited T cell reactivity to neuro-antigen in murine EAE, and the effects were dependent on TRAIL-R signaling. Moreover, TRAIL directly inhibited activation of MOG35-55-activated CD4+ T cells, resulting in suppression of neuroinflammation and reduced disease activity in adoptive transfer-induced EAE. Furthermore, TRAIL-R signaling inhibited phosphorylation of proximal T cell receptor (TCR) associated tyrosine kinases in activated CD4+ T cells. Importantly, TRAIL/TRAIL-R interaction downregulated TCR downstream signaling genes in RNA sequencing and transcriptome analysis. Conclusion: TRAIL/TRAIL-R interaction regulates CD4+ T cell activation in autoimmune inflammation, and directly suppresses T cell activation via inhibiting TCR signaling, suggesting that TRAIL-R serves as a novel immune checkpoint in T cell responses.